2020
DOI: 10.1039/d0ra00060d
|View full text |Cite
|
Sign up to set email alerts
|

Single crystals of mixed Br/Cl and Sn-doped formamidinium lead halide perovskites via inverse temperature crystallization

Abstract: FAPbBr3−xClx and doped FAPb1−xSnxBr3 perovskite single crystals were synthesized using inverse temperature crystallization (ITC). The single crystals displayed a bandgap tuneability of 2.05 eV to 2.57 eV and trap densities between 109 to 1011 cm−3.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
34
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(35 citation statements)
references
References 36 publications
1
34
0
Order By: Relevance
“…These studies demonstrated that the actual amount of Sn and Bi, incorporated in FAPb1-xSnxBr3 24 and Bi-doped MAPbX3 (X = Cl, Br, I) [29][30][31] single crystals respectively, was significantly less than the nominal percentages of Sn and Bi in the initial respective solution. In another example, the actual Cl% in FAPbBr3-xClx 24 crystals was found to be larger than the nominal value for Cl-poor target compositions (< 50% Cl) but smaller for Cl-rich reactions. Similar instances were also found for A-cation substitutions.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…These studies demonstrated that the actual amount of Sn and Bi, incorporated in FAPb1-xSnxBr3 24 and Bi-doped MAPbX3 (X = Cl, Br, I) [29][30][31] single crystals respectively, was significantly less than the nominal percentages of Sn and Bi in the initial respective solution. In another example, the actual Cl% in FAPbBr3-xClx 24 crystals was found to be larger than the nominal value for Cl-poor target compositions (< 50% Cl) but smaller for Cl-rich reactions. Similar instances were also found for A-cation substitutions.…”
Section: Introductionmentioning
confidence: 93%
“…Examples of nominal and actual composition mismatch in mixed-metal 24,[29][30][31][32] and mixed-halide 24 perovskite systems have been studied using X-ray photoelectron spectroscopy (XPS) and flame atomic absorption spectroscopy (FAAS). These studies demonstrated that the actual amount of Sn and Bi, incorporated in FAPb1-xSnxBr3 24 and Bi-doped MAPbX3 (X = Cl, Br, I) [29][30][31] single crystals respectively, was significantly less than the nominal percentages of Sn and Bi in the initial respective solution. In another example, the actual Cl% in FAPbBr3-xClx 24 crystals was found to be larger than the nominal value for Cl-poor target compositions (< 50% Cl) but smaller for Cl-rich reactions.…”
Section: Introductionmentioning
confidence: 99%
“…Although we chose to focus on MAPX SC, other types of perovskite highly promising for the solar industry were successfully grown as SC, and has been reviewed elsewhere (17,25,(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43). For example formamidinium lead halide perovskite FAPbX 3 and mixed cations perovskite FA (1≠x) MA x PbI 3 , as well as mixed halides perovskites and even FAPbBr 3≠x Cl x or FAPb 1≠x Sn x Br 3 , were succesfully grown by ITC (73)(74)(75)(76)(77)(78)(79). Lead free perovskite, MASnI 3 and FASnI 3 gaining increasing attention due to lead toxicity, were also successfully grown as SC by a top-seeded solution growth method (80).…”
Section: Inverse Temperature Crystallization -Itcmentioning
confidence: 99%
“…16,17 In addition to structural diversity, [18][19][20][21] other advantages of A-cation doping have been shown to include improved stability 22 and power conversion efficiency of photovoltaic devices, 23 and reduced trap states in the fabrication of solar cells. 24,25 For example, Saliba et al achieved high efficiency solar cells up to 21.6% with a mixed A-cation composition -(Rb,Cs,MA,FA)PbI3, which retained 95% power conversion efficiency after 500 hours at 85 ℃. 26 Prochowicz et al obtained a mixed A-cation solid solution system MAxFA1-xPbI3 by mechano-synthesis to stabilise the α-FAPbI3 cubic phase in air, which is a key absorber layer in high-efficient solar cells.…”
Section: Introductionmentioning
confidence: 99%
“…Any mismatch between nominal and actual composition may reduce the reliability of the conclusions drawn from subsequent structural and photophysical studies. Examples of nominal and actual composition mismatch in mixed-metal 24,[29][30][31][32] and mixed-halide 24 perovskite systems have been studied using X-ray photoelectron spectroscopy (XPS) and flame atomic absorption spectroscopy (FAAS). These studies demonstrated that the actual amount of Sn and Bi, incorporated in FAPb1-xSnxBr3 24 and Bi-doped MAPbX3 (X = Cl, Br, I) [29][30][31] single crystals respectively, was significantly less than the nominal percentages of Sn and Bi in the initial respective solution.…”
Section: Introductionmentioning
confidence: 99%